Modeling of 2-D Periodic Array of Dielectric Bars with a Low Reflection Angle for a Wind Tunnel High-Power Microwave Experiment - Rong Bao; Yang Tao; Yongdong Li (Applied Sciences, 2024)
Two-dimensional periodic dielectric bars have potential applications in high-power microwave (HPM) radiation effect experiments performed in wind tunnels. Such a bar is designed to consist of two types of dielectric materials, and two lined-up blocks can be considered as a period along the bar. Under plane excitation, the theoretical period length of the beat wave pattern fits well with the simulation result, which requires modifying the previously presented field-matching method. The phase distribution on the cross-section can be non-uniform when two different guiding modes are excited independently and propagate along different materials. Directional reflection with a low reflection angle can be obtained by reasonably choosing the parameters of the dielectric array. The designed array can decrease the returned-back microwave power toward the microwave source by 6 dB according to the numerical simulation, which included the wind tunnel, the input antenna, the test target, and the reflect array in one model.